THE APPLICATION OF SCAFFOLDING TECHNIQUES IN WRITING ABILITY OF ELEVENTH GRADE STUDENTS AT SMA NEGERI 1 SIANTAR - Dwi Fitria Anggraini; Leonita M.E. Manihuruk; Irene Adryani Nababan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Writing is one of the essential skills in English learning, yet many students face difficulties in generating ideas, organizing arguments, and applying appropriate linguistic features when composing analytical exposition texts. This study aims to investigate the effect of scaffolding techniques on the writing ability of eleventh-grade students at SMA Negeri 1 Siantar. A quantitative approach with a quasi-experimental design was employed, involving two groups: an experimental class taught using scaffolding techniques and a control class taught using conventional methods. Both groups completed a pre-test and post-test to measure their writing performance. The findings show that the experimental group experienced a significant improvement, with the mean score increasing from 50.50 to 82.74, while the control group increased from 50.71 to 72.12. The Wilcoxon Signed Rank Test and Mann-Whitney U Test revealed a significant difference between the two groups, with Asymp. Sig. (2-tailed) = 0.000, indicating that scaffolding had a positive and statistically significant effect. These results suggest that scaffolding through modeling, guided practice, feedback, and gradual release helps students better understand text structure, develop ideas, and apply appropriate language features. Therefore, scaffolding techniques are effective in enhancing students’ writing ability, particularly in composing analytical exposition texts.